2024
DOI: 10.1097/ccm.0000000000006055
|View full text |Cite
|
Sign up to set email alerts
|

Survival for Nonshockable Cardiac Arrests Treated With Noninvasive Circulatory Adjuncts and Head/Thorax Elevation*

Kerry M. Bachista,
Johanna C. Moore,
José Labarère
et al.

Abstract: OBJECTIVES: Cardiac arrests remain a leading cause of death worldwide. Most patients have nonshockable electrocardiographic presentations (asystole/pulseless electrical activity). Despite well-performed basic and advanced cardiopulmonary resuscitation (CPR) interventions, patients with these presentations have always faced unlikely chances of survival. The primary objective was to determine if, in addition to conventional CPR (C-CPR), expeditious application of noninvasive circulation-enhancing adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In prospective registry studies, rapid initiation of AHUP-CPR conveyed a high probability of ROSC, survival to hospital discharge, and survival with favorable neurologic function in OHCA, irrespective of the presenting rhythm [ 126 , 127 ]. Follow-up prospective observational studies of AHUP-CPR in non-shockable OHCA demonstrated similar findings, with an increased likelihood of survival to hospital discharge in the AHUP-CPR group as opposed to the conventional CPR group [ 126 , 128 ].…”
Section: Augmentation Of Circulatory Supportmentioning
confidence: 84%
“…In prospective registry studies, rapid initiation of AHUP-CPR conveyed a high probability of ROSC, survival to hospital discharge, and survival with favorable neurologic function in OHCA, irrespective of the presenting rhythm [ 126 , 127 ]. Follow-up prospective observational studies of AHUP-CPR in non-shockable OHCA demonstrated similar findings, with an increased likelihood of survival to hospital discharge in the AHUP-CPR group as opposed to the conventional CPR group [ 126 , 128 ].…”
Section: Augmentation Of Circulatory Supportmentioning
confidence: 84%